1975
DOI: 10.1172/jci108087
|View full text |Cite
|
Sign up to set email alerts
|

A natriuretic principle derived from kidney tissue of volume-expanded rats

Abstract: A S T R A CT Homogenates of kidneys from hydropenic and volume-expanded rats were subjected to gel filtration with Sephadex G-25. A fraction of the eluate coincident with the fourth UV peak was injected into the aorta of rats with one kidney excluded. A fraction eluting before the albumin peak was utilized as a control. Significant natriuresis and diuresis were observed after infusion of the fraction obtained from volumeexpanded kidneys but not after infusion of the fraction from hvdropenic kidneys or the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…After the elution of the salt peak (5), the osmolality dropped to Ͻ100 mOsm/kg. Following this step, ten 10-ml fractions were collected, lyophilized, resuspended (in 1.0 ml of water), and assayed for inhibition of SCC in the frog skin (10). Active fractions, as already defined, from the Sephadex column were then injected into a semiprep C18 column (Synergi 4u Hydro-RP 80A 250 ϫ 10 mm, 4 m; Phenomenex, Torrance, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the elution of the salt peak (5), the osmolality dropped to Ͻ100 mOsm/kg. Following this step, ten 10-ml fractions were collected, lyophilized, resuspended (in 1.0 ml of water), and assayed for inhibition of SCC in the frog skin (10). Active fractions, as already defined, from the Sephadex column were then injected into a semiprep C18 column (Synergi 4u Hydro-RP 80A 250 ϫ 10 mm, 4 m; Phenomenex, Torrance, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In numerous experimental models, several groups had consistently observed natriuretic activity from a small molecule (Ͻ1,000 Da) contained in mammalian urine that eluted as a postsalt peak in Sephadex G-25 gel chromatography. A natriuretic substance was shown to be present in urine and/or serum extracts of patients with chronic renal disease (CRD) (4,5), normal man (6), salt-loaded man (7,8), volume-loaded man (9), and volume-loaded rat (10). Although inferred in the experiments mentioned earlier, no molecule was ever isolated or identified.…”
mentioning
confidence: 97%
“…Previous work from this laboratory 14 has demonstrated that a natriuretic factor also can be isolated from kidneys of volume-expanded rats but is not found in kidneys of hydropenic rats. In the present study we have shown in addition that this factor inhibits transepithelial sodium transport by isolated frog skin in a dose-dependent manner.…”
mentioning
confidence: 88%
“…Fraction III from hydropenic rats was not tested because our earlier experiments had demonstrated clearly that the fraction from expanded, but not from hydropenic, rat kidneys contained natriuretic activity. 14 …”
Section: Rat Assay In Vivomentioning
confidence: 99%
See 1 more Smart Citation